Perfil populacional de soroconversão de IgG anti-SARS-CoV-2 entre 2020 e 2024 e avaliação prospectiva dos impactos imune-humorais do SARS-CoV-2 em um segmento de doadores de sangue - Sousa Júnior, Joaquim Cesar do Nascimento (2024)
The quantitative and qualitative investigation of the humoral response profile against SARS-CoV-2 (SC2) has been of paramount importance for evaluating exposure levels, reinfection, and seroconversion to viral antigens during the pandemic. This study evaluated a sample of 323 blood donors from HEMOCE, selected during the pandemic period (2020–2022) and post-pandemic period (September 2023 and April 2024). The study aimed to investigate associations of the humoral immune profile in subgroups of blood donors from the city of Fortaleza, between 2020 and 2024, correlating the effects of the SC2 pandemic with the donors' infection and vaccination history. Two specific tests against SC2 – anti-N and anti-S serum IgG – were used for this purpose. The analysis of anti-N IgG levels, comparing the pandemic period (2020 and 2021) with the post-pandemic period, showed significant increases (p < 0.05), reflecting a higher rate of infections during the early years of the pandemic. Similarly, a trend of decline in anti-S IgG levels was observed between 2022 and the post-pandemic period. For the paired vaccination analysis, participants were classified into groups and subgroups according to their vaccination dose records, showing a significant increase in anti-S IgG titers between the unvaccinated state (“Non-Immunized”) and the vaccinated states (p<0.001). Differences were observed between the subgroups “Vaccinated (D1-D4)” vs. “Bivalent” and “Initial Doses (D1-D2)” vs. “Bivalent” (p<0.001). For the cross-sectional analyses, anti-S IgG levels were associated with most self-reported variables (p<0.05), such as the number of reported infections, time since the last infection, vaccination status, and indices derived from the mental health questionnaire related to resilience and depression. Among the donors who reported having had COVID-19, 31.4% reported persistent symptoms, with the highest prevalence of “Memory Loss” in the “Medium” (31.8%) and “High” (25%) anti-S IgG groups. To evaluate the effects of antibody neutralization, a PRNT90 neutralization assay was performed against SC2 subvariants - GK.1 and JN.1 - which showed significant association with anti-S and anti-N IgG levels (p < 0.05; r > 0.60), with cutoff values estimated by sensitivity/specificity analysis (IgG anti-S > 50,165.14 BAU/mL; IgG anti-N > 1.03 Index (S/C)). Moderately, elevated leukocyte and lymphocyte levels were also associated with neutralizing activity (p<0.05; r>0.40). No correlations were found between total IgA, IgE, IgG, and IgM levels with PRNT90 results, nor between total IgG and anti-S IgG. These results emphasize the importance of seroepidemiological investigations at the population level, both for monitoring exposure/reinfection levels and vaccine-induced immune evasion, as well as serving as guides for prevention and intervention strategies for emerging diseases, both in a pandemic and post-pandemic context.